2022
DOI: 10.3389/fpubh.2022.833551
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of International Travel Arrivals on the New HIV Infections in 15–49 Years Aged Group Among 109 Countries or Territories From 2000 to 2018

Abstract: ObjectiveThe prevalent international travel may have an impact on new HIV infections, but related studies were lacking. We aimed to explore the association between international travel arrivals and new HIV infections in 15–49 years aged group from 2000 to 2018, to make tailored implications for HIV prevention.MethodsWe obtained the data of new HIV infections from the Joint United Nations Programme on HIV/AIDS and international travel arrivals from the World Bank. Correlation analysis was used to explore the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These cities are highly touristic, and sexual tourism can be implied for the expansion of the HIV epidemic. A previous study showed a possibility of 6.61% HIV infection in people aged 15-49 years old for evey 1,000,000 increment in internation arrivals (47).…”
Section: Discussionmentioning
confidence: 94%
“…These cities are highly touristic, and sexual tourism can be implied for the expansion of the HIV epidemic. A previous study showed a possibility of 6.61% HIV infection in people aged 15-49 years old for evey 1,000,000 increment in internation arrivals (47).…”
Section: Discussionmentioning
confidence: 94%
“…There are several objective conditions for the development of infectious diseases: the active development of tourism [ 1 , 2 , 3 ], the increase in migration processes [ 4 , 5 , 6 , 7 , 8 ], returning and re-emerging diseases [ 9 , 10 ], as well as the likelihood of using pathogens of various infectious diseases as biological weapons [ 11 , 12 , 13 ]. Improved social and environmental conditions help with reducing the risk of contracting and spreading infectious diseases [ 14 , 15 ], but, paradoxically, as the living standards rise, the mortality from some of them also increases.…”
Section: Introductionmentioning
confidence: 99%